FORMATION OF MARKETING AND LOGISTICS SYSTEM OF INDUSTRIAL ENTERPRISE - NYZHNYK, VICTOR; SHARKO, VITALIY; GROMOVA, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Marketing and logistics are two such areas, the synergy of achieving the goals of which opens up competitive potential for the company, increases the profit margin and keeps the company's brands in the field of customer loyalty.Modern European, American and domestic scientific developments have been thoroughly proven and disclosed in numerous publications by scientists and practitioners. However, given the globalization process, resource constraints, automation and other features of today's Ukrainian business environment, management tools of American and European practitioners can not fully meet the needs of entrepreneurship in Ukraine.The article reveals the basic criteria of relationship between marketing and logistic. The formation mechanism of marketing and logistic system at the enterprise is provided. The recommendations of organization balanced marketing and logistic system at the enterprise for a functional sign are formulated.It is proved that the introduction of marketing and logistics services at the enterprise is most appropriate to carry out the joint efforts of enterprise management and consultants. Moreover, the task of consultants should include, on the one hand, methodological support for the restructuring of sales, marketing, logistics, and on the other hand - training the management team to modern approaches and methods of implementing marketing and logistics system in the enterprise as a whole.
Keywords: industrial enterprise; marketing; logistics; marketing and logistics service